KONTRIBUSI MOTIVASI DAN PEMANFAATAN FASILITAS BELAJAR TERHADAP HASIL BELAJAR DASAR LISTRIK ELEKTRONIKA - Boy Ichsan Herianto; Putra Jaya (Universitas Negeri Padang, 2019)
This study aims to determine the Contribution of Learning Motivation and Utilization of Learning Facilities Against Basic Electrical and Electronic Learning Outcomes Grade X Students of Audio Video Engineering Skills Program at SMK Negeri 5 Padang. The population in this study amounted to 63 students. This type of research is correlational descriptive. In this study using Simple Random Sampling with a total of 56 students. Data Learning outcomes were obtained from Elementary and Electrical subject teachers at SMK Negeri 5 Padang. Meanwhile Motivation Learning Data and Learning Facilities Utilization obtained by using a questionnaire with a Likert scale that has been tested for validity and reliability. The results of data analysis showed: (1) Motivation to Learning and Utilization of Learning Facilities together contributed 36.24% to learning outcomes; (2) Learning Motivation contributes 7.95% to learning outcomes; (3) Utilization of Learning Facilities contributes 25.50% to learning outcomes. So it can be concluded that the motivation to learn and use learning facilities contributes to the learning outcomes of basic electricity and electronics at SMK Negeri 5 Padang.Keywords: Learning Motivation, Utilization of Learning Facilities, Learning Outcomes